Origin and characteristics of unbalanced chromosome aberrations in therapy-related myelodysplasia and acute myeloid leukemia (Hematology Meeting Reports, 2009)
Abnormalities of chromosomes 5 and 7, the most frequent cytogenetic aberrations in t-MDS and t-AML, are associated with therapy with alkylating agents and have poor prognostic impact. However, cytogenetic and molecular studies of patients with t-MDS and t-AML show that abnormalities of chromosomes 5 and 7 clearly define different genetic pathways. Thus, cases with -5/5q- with or without abnormalities of chromosome 7 are characterised by mutations of the TP53 gene, a complex karyotype, deletion or loss of 17p, and gain of chromosome band 11q23 with amplification of the MLL gene. Cases with -7/7q- and normal chromosomes 5 on the other hand are characterised by a simpler karyotype, somatic mutations of the AML1/RUNX1 gene and frequent methylation of the p15 promoter. The origin of hypoploidy, a frequent phenomenon in t-MDS and t-AML, will be discussed.